Production Process Analysis of Ginger, Lemongrass, Cinnamon Instant Drink “Jesika” - Lina Widawati; Hesti Nur'aini; Jurois Meksi (SINTA Journal (Science, Technology, and Agricultural), 2022)
Ginger, lemongrass and cinnamon instant drink “jesika” is herbal drink in powder with natural ingredients produced by Badan Usaha Milik Desa (BUMDES) Manfaat in Sukasari Village, Air Periukan Sub District, Seluma District, Bengkulu Province. The purpose of this research is to analyze the production process, mass balance, chemical analysis and business analysis of jesika instant drink. The methods used include observation and interviews, chemical analysis and business analysis. The results showed that in the processing of jesika instant drink, from of the total raw material of 64,5 kg,  the finished material was 52,5 kg. From the results of chemical analysis of the instant drink jesika, it was found that the water content of the instant drink jesika was 7,82%, the ash content was 1,98%, and the antioxidant was 102,32 mg/ml. Based on the analysis of the business of producing instant drink jesika, the income obtained by the producer for one time of production gets an net profit Rp.3.185.000,-